Effect of electron beam irradiation on the property of oat and barley proteins and their interaction with major flavor compounds - Junhao Li; Yue Tang; Dichen Ying; Zhanchang Hu; Tianyu Qian; Yan Chen; Zhiyang Yu; Zhen Yang (Food Chemistry, 2026)

Analyzing Muscle Contraction Dynamics Through Continuous Vector Segmentation and Tracking - Wenze Wu; Wenyu Chen; Liuhe Li; Junnan Feng; Zhe Liu; Wei Gu; Lin Gao; Jiankang He; Dichen Li (Annals of Biomedical Engineering, 2026)

Structured wave-transparent metamaterials for simultaneous broadband electromagnetic and acoustic absorption - Tongtong Zhang; Qingxuan Liang; Yubing Duan; Xin Yan; Aoqi Ren; Jiaming Feng; Dichen Li (Chemical Engineering Journal, 2026)

Paper garland-inspired 2D single-phase spiral folded-rod elastic metamaterial for extremely low-frequency vibration isolation - Kai Miao; Leilei Wang; Wencheng Yin; Rui Zhang; Shuyuan Liu; Facheng Song; Jian Zhu; Lingling Wu; Jianhui Liang; Dichen Li; Ling Wang (Engineering Structures, 2026)

Spatial heterogeneity of gully erosion and its dominants in multiple spatial scales in the Rolling Hilly Region of Northeastern China - Xin Liu; Dichen Wang; Yulan Chen; Dan Li (Geomorphology, 2026)

A Fiber-Driven Finite Element Model for Predicting Residual Limb Soft Tissue Deformation: Applications in Prosthetic Socket Design - Ling Wang; Ziyan Qiu; Lei Tang; Fuhao Huang; Pingping Wei; Senay Mihcin; Changning Sun; Hongyuan Zhao; Lei Shi; Song Han; Dichen Li (Annals of Biomedical Engineering, 2026)

3D bioprinted NSC-EVs hydrogel scaffold promotes sustained functional repair via autophagy activation after TBI in mice - Lei Zhang; Guangliang Chen; Jinwei Pang; Hao Tian; Kecheng Guo; Jimin He; Guojin Shang; Chuying Wang; Liu Yang; Xiao Rao; Kuangyang Yu; Dichen Li; et al. (Chemical Engineering Journal, 2025)

Dual-mode aptasensor based on P-CeO2NR@Mxene and exonuclease I-assisted target recycling for malachite green detection - Mingyue Ye; Xianfeng Lin; Jin Li; Xiaowan Chen; Dichen Ying; Shijia Wu; Zhouping Wang; Nuo Duan (Food Chemistry, 2024)

Multifunctional magnetic composite nanomaterial for Colorimetric-SERS Dual-Mode detection and photothermal sterilization of Vibrio parahaemolyticus - Jin Li; Xianfeng Lin; Jiajun Wu; Dichen Ying; Nuo Duan; Zhouping Wang; Shijia Wu (Chemical Engineering Journal, 2023)

Novel mutation in LRP5 gene cause rare osteosclerosis: cases studies and literature review - Dichen Zhao; Lei Sun; Wenbin Zheng; Jing Hu; Bingna Zhou; Ou Wang; Yan Jiang; Weibo Xia; Xiaoping Xing; Mei Li (Molecular Genetics and Genomics, 2023)
To study the effects of low-density lipoprotein receptor-related protein 5 ( LRP5 ) gene mutations on bone, and to open up our view of LRP5 and Wnt pathways on bone mass regulation. Three patients with increased bone mineral density or thickened bone cortex were included, who were 30-year-old, 22-year-old and 50-year-old men, respectively. The latter two patients were son and father of a same family. The characteristics of bone X-rays were evaluated in detail. Bone turnover markers were detected, such as procollagen type 1 amino-terminal peptide (P1NP), alkaline phosphatase (ALP), and type 1 collagen carboxyl terminal peptide (β-CTX). Dual energy X-ray absorptiometry (DXA) was used to measure the bone mineral density (BMD) at lumbar spine and proximal femur of the patients. The targeted next-generation sequencing (NGS) technology was used to detect pathogenic gene mutations, which were further verified by Sanger sequencing. Moreover, the gene mutation spectrum and phenotypic characteristics of reported patients with LRP5 gain-of-function mutations were summarized by reviewing the literature. The main characteristics of the first patient were headache, facial paralysis, high BMD (lumbar vertebrae 1–4: 1.877 g/cm 2 , Z-score: 5.8; total hip: 1.705 g/cm 2 , Z-score: 5.7), slightly increased P1NP (87.0 ng/mL) and β-CTX (0.761 ng/mL) level, and with thickened bone cortex, especially the cranial vault. The latter two patients showed enlargement of the mandible and enlarged osseous prominence of the tours palatinus. X-rays showed that the bone cortex of skull and long bones were thickened. The bone turnover markers and BMD were normal. All three cases carried novel missense mutations in LRP5 gene, which were mutation in exon 3 (c.586 T > G, p.Trp196Gly) of the first patient, and mutation in exon 20 (c.4240C > A, p.Arg1414Ser) of the latter two patients. Combined with the reported literature, a total of 19 gain-of-function mutations in LRP5 were detected in 113 patients from 33 families. Hotspot mutations included c.724G > A, c.512G > T and c.758C > T. Furthermore, mutations in the exon 3 of LRP5 may cause severe phenotypes. LRP5 gain-of-function mutations can lead to rare autosomal dominant osteosclerosis type Ι (ADO Ι), which was characterized by increased bone mass and thickened bone cortex. In-depth research on the Wnt pathway will be benefit for discovering important mechanisms of bone mass regulation.